Repeated aerial diving, and aerial ingestion of small schooling fish, probably Bilih Mystacoleucus padangensis, by Brahminy Kite - Janra, Muhammad N. (KUKILA, 2017)
Many papers have been published on the food and feeding behaviour of the Brahminy Kite Halistur indus. At Singkarak Lake, West Sumatra, a Brahminy Kite was observed repeatedly diving from 10-15 m in the air to snatch small fish from the surface of the water, and eating them in the air. The prey was probably Bilih Mystacoleucos padangensis, a fish species endemic to the lake. Only one fish was taken on each dive, so it was undoubtedly more energy-efficient to eat the prey on the wing than to take it to a perch after each capture, though potential kleptoparasitism by other raptors may have also selected for this feeding behaviour.